E-Commerce and the Rural Sector in Pangandaran - Endang Amalia (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the modern times E-commerce is giving a tough competition to the traditional trade and business. Due to the advancement of technology the world has become a global village. E-commerce has reached most of the consumers in the urban sector, but the challenge lies in front of the companies so that it reaches the rural sector also. The rural population of Indonesia has to go at distant places or nearby cities to purchase local products especially in Pangandaran District. Here E-commerce can come to their help by widening its area of operations.